Caracterización química de suelos cultivados con algodón (Gossypium Hirsutum L.) en Santa Fe, Argentina - Mieres, Luciano Nicolás; Scarpin, Gonzalo Joel; Zorzón, Cristian; Sponton, Julio Marcelo; Monzon, Leonardo Jesús; Ardit, Gabriel (Asociación Argentina de la Ciencia del Suelo (AACS), 2024)
Póster de la presentación